Nucleation field and energy product of aligned two-phase magnets - progress towards the '1 MJ/m3' magnet - COEY, JOHN MICHAEL DAVID (IEEE, 1993)
Exchange hardening of nanostructured two-phase systems composed of an aligned hard phase and a soft phase with high magnetization is investigated using a micromagnetic approach which accounts for intereactions between the soft regions. For Sm2Fe17N3 (2.5 nm)/Fe65Co35(9nm) multilayers an energy product as high as 1 MJ/m3 (120 MGOe) is predicted, with a rare-earth content of only 5wt%. Giant energy products may also be achieved in suitable cellular and disordered structures.
PUBLISHED
Keywords: Physics